FTY720 blocks egress of T cells in part by abrogation of their adhesion on the lymph node sinus - Zhi, Liang; Kim, Pilhan; Pitsillides, Costas (My University, 2011)
Egress of lymphocytes from lymphoid tissues is a complex process in which Gαi-mediated signals play a decisive role. We show here that although FTY720, an agonist of the sphingosine 1-phosphate (S1P)1 receptor, induces S1P1 receptor internalization sufficiently in the presence or absence of Gαi2 or Gαi3, the drug blocks egress of wild-type (WT) and Gαi3-deficent T cells, but not Gαi2-deficient T cells, in both WT and Gαi2-deficient hosts. Intravital imaging of lymph nodes revealed that all three groups of T cells approached and engaged cortical sinusoids similarly in the presence or absence of FTY720. The cells also entered and departed the sinus at an almost identical frequency in the absence of the drug. However, after engagement of the sinus, most WT and Gαi3-deficient T cells retracted and migrated back into the parenchyma in FTY720-treated animals, due to a failure of the cells to establish adhesion on the sinus, whereas Gαi2-deficient T cells adhered firmly on the sinus, which prevented their retraction, facilitating their transmigration of the lymphatic endothelial barrier. These data confirm egress of Gαi2−/− T cells independent of S1P-mediated chemotaxis and failure of FTY720 to close lymphatic stromal channels and argue for the first time, to our knowledge, that FTY720 induces lymphopenia in part by impairing T cell adhesion to the sinus in a manner dependent on Gαi2
Keywords: Immunology; T cells; Lymph nodes; Mice; Animal experimentation; Cell adhesion